Electrochemically Effective Surface Area of a Polyaniline Nanowire-Based Platinum Microelectrode and Development of an Electrochemical DNA Sensor - Luyen Thi Tran; Hoang Vinh Tran; Ha Hong Cao; Thuy Hong Tran; Chinh Dang Huynh (Journal of Nanotechnology)
Electrochemical DNA sensors based on nanocomposite materials of polyaniline nanowires (PANi NWs) have been published in the literature. However, it is interesting that there are very few research studies related to the development of electrochemical DNA sensors based on PANi NWs individually. In this study, PANi NWs were synthesized site-specifically on a Pt microelectrode with only 0.785 mm2 area using an electropolymerization procedure. The electrosynthesis allows direct deposition of PANi NWs onto the Pt microelectrode in a rapid and cost-effective way. The good properties of PANi NWs including uniform size, uniform distribution throughout the Pt working electrode, and H2SO4 doping which improved the conductivity of the PANi material were obtained. Especially, the electrochemically effective surface area of the PANi NW-based Pt microelectrode determined in this work is nearly 19 times larger than that of the Pt working electrode. The PANi NW layer with large electrochemically effective surface area and high biocompatibility is consistent with the application in electrochemical DNA sensors. The fabricated DNA sensors show advantages such as simple fabrication, direct detection, high sensitivity (with the detection limit of 2.48 × 10−14 M), good specificity, and low sample volume requirement. This study also contributes to confirm the role of PANi NWs in DNA probe immobilization as well as in electrochemical signal transmission in the development of electrochemical DNA sensors.